2003
DOI: 10.1210/en.2002-221033
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Proopiomelanocortin Neurons Are Glucose Responsive and Express KATPChannels

Abstract: Hypothalamic proopiomelanocortin (POMC) neurons are critical for controlling homeostatic functions in the mammal. We used a transgenic mouse model in which the POMC neurons were labeled with enhanced green fluorescent protein to perform visualized, whole-cell patch recordings from prepubertal female hypothalamic slices. The mouse POMC-enhanced green fluorescent protein neurons expressed the same endogenous conductances (a transient outward K(+) current and a hyperpolarization-activated, cation current) that ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
253
3
8

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 331 publications
(287 citation statements)
references
References 56 publications
18
253
3
8
Order By: Relevance
“…Fluorescent cells or adjacent nonfluorescent cells were patched and then harvested into the patch pipette by applying negative pressure. The contents of the pipette were expelled into a siliconized microcentrifuge tube containing 1 l of 5ϫ Colorless GoTaq Flexi buffer (Promega, Madison, WI), 15 U of Rnasin, 0.5 l of 100 mM DTT, and DEPC-treated water in a total volume of 5 l. Each harvested cell was reverse transcribed as described previously (Ibrahim et al, 2003;Qiu et al, 2003). Briefly, the harvested cell solution and 25 ng of hypothalamic total RNA in 5 l were denatured for 5 min at 65°C, and then cooled on ice for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Fluorescent cells or adjacent nonfluorescent cells were patched and then harvested into the patch pipette by applying negative pressure. The contents of the pipette were expelled into a siliconized microcentrifuge tube containing 1 l of 5ϫ Colorless GoTaq Flexi buffer (Promega, Madison, WI), 15 U of Rnasin, 0.5 l of 100 mM DTT, and DEPC-treated water in a total volume of 5 l. Each harvested cell was reverse transcribed as described previously (Ibrahim et al, 2003;Qiu et al, 2003). Briefly, the harvested cell solution and 25 ng of hypothalamic total RNA in 5 l were denatured for 5 min at 65°C, and then cooled on ice for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…In a series of studies we have found that hypothalamic ␣-melanocyte-stimulating hormone, which is produced from the proopiomelanocortin (POMC) precursor and is preferentially reduced during aging [68][69][70][71][72][73], is reduced by fasting and in genetic obesity [74], and is reduced by gold thioglucose [75]. POMC neurons are stimulated by glucose and other nutritional factors [76], and transgenic correction of reduced hypothalamic POMC corrects impairments in glucose homeostasis in obese mice [77]. Thus age-related impairments in hypothalamic POMC could plausibly contribute to age-related obesity and metabolic impairments.…”
Section: Potential Cumulative Toxic Effect Of Glucose On Neuroendocrimentioning
confidence: 99%
“…Changing levels of extracellular glucose can lead to either excitation or inhibition of glucosesensitive hypothalamic neurons. Neurons excited by rising glucose behave similarly to the ␤ cells of the endocrine pancreas (Ibrahim et al, 2003). In these cells, an increase in glucose metabolism gives rise to elevated ATP levels that promote closure of ATP-sensitive K ϩ channels (K ATP ) and depolarization.…”
Section: Introductionmentioning
confidence: 99%